At Least Curry Puff / Mohamad Azim Jahya - Jahya, Mohamad Azim (2021)
I have chosen to run a small food business which is my brand name is At Least Curry Puff. My main business activity is selling frozen curry puff which is been produce by me and also contributed by my mother and my neighbours. I am offer two types of curry puff filling which is potato and sardines. The production process is located at my family home and the food ingredient are been bought from the shop near my house. I have chosen this type of business as my educational purposes for the subject of Principle of Entrepreneurship (ENT530) because I am interested in food business and at the same time curry puff is my favourite snack food. I want to share to people my lovely mother and my neighbours curry puff recipes through this business. This individual assignment instructs the student to implement social media which is Facebook to run the business. This is the new challenge but also it is interesting in today’s business. I am also registered my business at Go-Ecommerce which is under the Malaysia Digital Economy Corporation (MDEC). With this registration, I can key-in my business revenue, gross profit, loss, and other information and data which is it is make me easily track my business flow. This is good initiative that produce my MDEC in order to help the businesses improvement of quality and to be more efficient and effective. There are certain difficulties in order for me to run this business because I am the first timer to run a business and also lack of experience in selling and promoting skill of the product. Another barrier for me is the Movement Control Order (MCO) that instructed by government which is affect my business. The Standard Operating Procedure (SOP) during this MCO is restrict us from go outside from the house not more than 10KM have affecting my product delivery process since I am using Cash on Delivery (COD) method which delivered by myself to customer by using my own motorcycle. Last but not least, even this is for educational purposes only, I am felt very exciting to run this business after this because I take this subject as my adding value to find my skill and knowledge of selling, promoting, and manage the business.